Zakat Profesi Perspektif Dewan Hisbah Persis - Mohamad Ma’mun; Mu’min Firmansyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The term professional zakat is a contemporary treasure, because at the time of the Prophet Muhammad Saw, was not yet known this term. Yusuf al-Qardhawi was a cleric who introduced the zakat of this profession. Because it is a contemporary scholar for which there is no express answer in the Qur'an and Hadith, the discussion of zakat profession is interesting and there are several different opinions. Some say mandatory, some don't, and some give input to professions that generate money income are subject to mandatory. Persis through its Hisbah council gives a legal decision, that there is no obligation to zakat profession. Zakat is a worship whose legal determination must be through the Qur'an or al-Hadith. Meanwhile, in both verses are not found. However, Persis provides provisions, for professions even though they are not subject to mandatory zakat, but are subject to mandatory philanthropy whose nominal amount is adjusted to the needs of Muslims.